Grain size effects on dislocation and twinning mediated plasticity in magnesium. (February 2016) - Fan, Haidong; Aubry, Sylvie; Arsenlis, Athanasios; El-Awady, Jaafar A.
Abstract: Grain size effects on the competition between dislocation slip and 10 1 ¯ 2 -twinning in magnesium are investigated using discrete dislocation dynamics simulations. These simulations account for dislocation–twin boundary interactions and twin boundary migration through the glide of twinning dislocations. It is shown that twinning deformation exhibits a strong grain size effect; while dislocation mediated slip in untwinned polycrystals displays a weak one. This leads to a critical grain size at 2.7 μm, above which twinning dominates, and below which dislocation slip dominates. Graphical abstract: